Experiences of African Americans Living With Sickle Cell Disease. (May 2022) - Wickersham, Karen E.; Dawson, Robin M.; Becker, Karen P.; Everhart, Kayla C.; Miles, Heather S.; Schultz, Beth E.; Tucker, Curisa M.; Wright, Pamela J.; Jenerette, Coretta M.
Introduction: About 100, 000 individuals in the United States live with sickle cell disease (SCD). Palliative care (PC) can improve symptom management for these individuals. The purpose of the study was to explore (a) the experiences of people living with SCD, and (b) their knowledge and perceptions of PC. Method: Using a qualitative, descriptive design, adults with SCD were recruited from a foundation in the southeastern United States. Data included social and SCD-related demographics and audio-recorded, semi-structured focus groups. Analysis took a thematic analysis approach. Results: Participants: There were 16 African Americans who participated in the study, 75% of whom were females, and aged 22 to 71 years. Five themes were identified: unique and unpredictable impact of SCD on daily life, the changing experience of SCD over time, stigmatization/marginalization in health care interactions, perceptions of support in managing SCD symptoms/crises, and PC: "What is it?" Discussion: Participants lacked PC knowledge. PC should be offered to individuals with SCD as part of comprehensive SCD management.